DAMPAK INKLUSI KEUANGAN TERHADAP RISIKO KREDIT PADA PERBANKAN DIGITAL DI INDONESIA PERIODE TAHUN 2015-2021 - Badrani, Donny Syah; Pangestuty, Farah Wulandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
One of the most significant risks for banks, including digital banks, is credit risk. Bank credit risk can be influenced by a number of things, one of which is increasing financial inclusion. Then there is the prime lending rate which is used as a variable control in this study. The purpose of this study is to identify and analyze the impact of financial inclusion on credit risk in Indonesian digital banks. This study employs panel data from four Indonesian digital banks from 2015 to 2021. Panel data regression is the regression model that was used, and the hypothesis was tested with the t test, the F test, and the coefficient of determination. Financial inclusion has a positive and insignificant effect on digital bank credit risk in Indonesia on the accessibility dimension, a negative and significant effect on the usage dimension, and for prime lending rates it has a positive and insignificant effect on digital bank credit risk in Indonesia. This indicates that digital banks in Indonesia can reduce their credit risk by utilizing financial services. So that increasing financial inclusion through the use of financial services must be further improved while still paying attention to the prudence principle.